Three-dimensional poly lactic-co-glycolic acid scaffold containing autologous platelet-rich plasma supports keloid fibroblast growth and contributes to keloid formation in a nude mouse model. Issue 1 (January 2018) - Chen, Chunlin; Wang, Haibin; Zhu, Guozhang; Sun, Zhongsheng; Xu, Xiang; Li, Fangwei; Luo, Shengkang
Highlights: To create 3D PLGA scaffolds containing PRP as in vitro culture environment for KL. To study their implantation into nude mice to mimic the process of keloid formation. Three-dimensional PLGA scaffold containing PRP supports keloid fibroblast growth. Three-dimensional PLGA scaffold contributes to keloid formation in a nude mouse model. Abstract: Background: There is a lack of proper animal models to study keloid formation. Aim: To create three-dimensional poly lactic-co-glycolic acid (PLGA) scaffolds containing autologous platelet-rich plasma (PRP) as an in vitro culture environment for keloid fibroblasts (KL), and to study their implantation into nude mice to mimic the process of keloid formation. Methods: Normal fibroblasts (FB) and KL cells were isolated from surgical specimens and transduced with lentivirus loaded with green fluorescent protein (GFP) and luciferase genes. The FB and KL cells were three-dimensionally cultured for 14–18 days in PLGA scaffolds containing PRP. Ten mice were implanted with KL cells in their left forelimbs(KL), and FB-scaffolds (FB + PLGA) in their right forelimbs. An additional ten mice were implanted with PLGA scaffolds without cells (PLGA) in their left forelimbs, and KL-scaffolds (KL + PLGA) in their right forelimbs. Graft volume and collagen content were analyzed 120 days after the implantation. Results: in vivo luminescence cell imaging showed that the FB cells proliferated in the PLGA scaffolds within 60 days after implantation, and reached a plateau afterwards until 120 days after implantation. The KL cells continuously proliferated in the PLGA scaffolds until 120 days after implantation. The KL + PLGA group showed higher graft volumes than the FB + PLGA group 120 days after the implantation (median volume, 166.95 vs. 63.34 mm 3 ); however, the difference is not statistically significant ( P = 0.743), due to a large variation of the graft volume within each group. Furthermore, Sirius red staining revealed increased collagen I deposition, and immunohistochemistry showed large-scale accumulation of α-smooth muscle actin (α-SMA), collagen I, and collagen III in the KL + PLGA grafts. Conclusion: The three-dimensional PLGA scaffold containing PRP supports keloid fibroblast growth and contributes to keloid formation in a nude mouse model.